Update Knowledge on Integrated Risk Management with Health Services at Yogyakarta Hospital, Indonesia - Fatma Siti Fatimah; Choirul Anwar; Raden Jaka Sarwadhamana; Imram Radne Rimba Putri; Ari Susiana Wulandari; Eliza Dwinta; Anafrin Yugistyowati; Edi Sampurno Ridwan; Mahfud Mahfud; Nara Arumbinang; Tia Ageng Kirana; Zamroni Zamroni; Noviyani Leksomono (Peneliti Teknologi Teknik Indonesia, 2023)
The research results showed a high level of implementation of clinical risk management (MRK) (77.78%). Risk management is an effort to analyze existing systems for potential errors to prevent incidents from occurring. Risk management is an organized effort to identify, prioritize risks, analyze and reduce potential risks that may occur to patients, visitors, staff and organizational assets. Hospital risk management can implement a policy design to prevent Adverse Events that harm patients. Community service activities through knowledge updates on integrated risk management with health services to increase the knowledge of health workers. This service method uses 3 stages of preparation for implementation through training and evaluation, with 51 participants taking part. As a result of this service to the community, there are still many health workers who have never attended training or seminars on risk management, as many as 34 health workers. Health workers already know about patient safety targets, after carrying out community service activities. Health workers already understand risk management